2013
DOI: 10.1002/chem.201301365
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Electronic and Steric Effects on the Insertion and Polymerization Reactivity of Phosphinesulfonato PdII Catalysts

Abstract: Thirteen different symmetric and asymmetric phosphinesulfonato palladium complexes ([{((X)1-Cl)-μ-M}n], M=Na, Li, 1=(X) (P^O)PdMe) were prepared (see Figure 1). The solid-state structures of the corresponding pyridine or lutidine complexes were determined for ((MeO)2)1-py, ((iPrO)2)1-lut, ((MeO,Me2))1-lut, ((MeO)3)1-lut, (CF3) 1-lut, and (Ph)1-lut. The reactivities of the catalysts (X) 1, obtained after chloride abstraction with AgBF4 , toward methyl acrylate (MA) were quantified through determination of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 64 publications
0
28
0
1
Order By: Relevance
“…Under these pseudo‐first‐order conditions, the first insertion of MA into the PdMe bond to give the first insertion product X 2 + ‐A MA is fast at 25 °C for all cationic complexes and is complete within about 30 min. The net rate constants k 1st of the first insertion are in the range (2.0–3.5)×10 −3 s −1 (Table 3, runs 1–6),20 which is close to the rate constant for PSO3 1′‐NaCl ( k 1st =3.2×10 −3 s −1 at 25 °C) 19a. The observed ratios of 2,1 to 1,2 regioselectivity in the first insertion product are about 10:1, 6:1, and 11:1 for H 1 + ‐A , DIPP 1 + ‐ A , and CF3 1 + ‐A respectively.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Under these pseudo‐first‐order conditions, the first insertion of MA into the PdMe bond to give the first insertion product X 2 + ‐A MA is fast at 25 °C for all cationic complexes and is complete within about 30 min. The net rate constants k 1st of the first insertion are in the range (2.0–3.5)×10 −3 s −1 (Table 3, runs 1–6),20 which is close to the rate constant for PSO3 1′‐NaCl ( k 1st =3.2×10 −3 s −1 at 25 °C) 19a. The observed ratios of 2,1 to 1,2 regioselectivity in the first insertion product are about 10:1, 6:1, and 11:1 for H 1 + ‐A , DIPP 1 + ‐ A , and CF3 1 + ‐A respectively.…”
Section: Resultsmentioning
confidence: 53%
“…19 The electronic and steric effects of the phosphine–sulfonate on the insertion reactions have been studied extensively, but a clear and general picture was not obtained 9b. 18, 19a,b …”
Section: Resultsmentioning
confidence: 99%
“…[60][61][62] Since the seminal applications in copolymerization, it was shown that the combination of various phosphinoarylsulfonic acids with [Pd(dba) 3 ] generated active species for these transformations. It should be noted that in the case of DMF as the L 0 ligand, the resulting complex is unstable and undergoes fast oligomerization.…”
Section: B-limentioning
confidence: 99%
“…Acrylates were initially copolymerized with ethylene at 60-80 C in various solvents in the presence of a catalytic system generated in situ from Pd(OAc) 2 or Pd(dba) 2 and bis(2-methoxyphenyl)phosphinobenzenesulfonic acid. 45,53,58,60,61,[115][116][117] Different polyethylene elastomers with specific physical properties were prepared with this copolymerization protocol starting from ethylene and acrylates featuring epoxide, silicon, or fluorinated functional groups 118 or easily hydrolyzed into the corresponding acids. 41 Copolymerization of ethylene with methyl acrylate was selected as the model reaction to evaluate the general mechanistic features and the influence of the experimental parameters of this reaction.…”
Section: Copolymerization Of Ethylene With Polar Monomersmentioning
confidence: 99%
“…d 8 Square planar metal alkyl complexes represent another important class of homogeneous catalysts. In particular, cationic α ‐diimine Ni(II) and Pd(II) methyl complexes and related complexes have been developed as alternative polymerization catalysts to traditional d 0 metallocene or Ziegler ‐type systems, with the advantage of being tolerant towards olefins bearing polar functional groups . The functional group tolerance of these d 8 complexes has allowed for the copolymerization of unfunctionalized α ‐olefins with polar vinyl monomers such as methyl acrylate .…”
Section: Introductionmentioning
confidence: 99%